How far can EPTs fly? A comparison of empirical flying distances of riverine invertebrates and existing dispersal metrics - Peredo Arce, Andrés (2021)
The species composition of a community is driven by the dispersal capacity of the species forming that community and their ecological niche. While the ecological niches of EPTs (Ephemeroptera, Plecoptera and Trichoptera) are well-studied due to their wide use as indicators for the ecological status of freshwater ecosystems, their dispersal capacity has not yet been accurately characterized. Dispersion of the merolimnic EPT species during the terrestrial aerial adult stage is of special importance because the distance dispersed by active flight or passive wind drift is usually much larger compared to dispersion during the aquatic larval stage by active crawling or by drifting downstream. The aerial dispersal distance has been directly measured for only a small number of EPT species. For most other species, the dispersal capacity is assessed indirectly using species’ traits that are mainly based on expert judgement and dispersal indices derived from trait information. In this study, we compiled a database of European EPTs’ aerial dispersal distances reported in empirical studies and compared them to the dispersal capacity of the species as described by five different dispersal indices (original and modified versions of Li’s Dispersal Capacity Metric DCM and Sarremejane’s Species Flying Propensity SFP as well as relative wing length). The database included empirical data on 180 species, comprising 9.3% of European EPT species. Most data came from trap experiments with traps located at different distances from the assumed emergence point. Since the distance classes differed between studies and had to be translated to a fixed set of four distance classes here, several species had to be assigned to more than one class. To account for this uncertainty, five ordered logistic regression models, each one with a dispersal index as predictor and the ordinal-scaled aerial dispersal distance as response, were bootstrapped 10,000 times. In each run, species belonging to several distance classes were randomly assigned to a single class out of all possible classes. Since wing length had no significant effect on aerial dispersal distance in any of the 10,000 bootstrap runs, we question the use of this anatomical trait as an indicator for the aerial dispersal capacity. In contrast, a modified version of the DCM index was consistently related to the aerial dispersal distances (96%). The original SFP index had a significant effect in 100% of the model runs, indicating that this index is very well-suited as an indicator for the aerial dispersal capacity of European EPT species. This study facilitates the assessment of European EPT flying distances by providing a compilation of empirical data on the topic and by recommending an accurate indirect method when empirical data is not available